2016
DOI: 10.36876/smjnt.1003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Association between Hyperuricemia and Contrast InducedAcute Kidney Injury in Patients with Acute ST-Elevation Myocardial Infarction Undergoing Percutaneous Coronary Intervention

Abstract: Background:The association between Hyperuricemia (HUA) and Contrast Induced-Acute Kidney Injury (CI-AKI) has not been extensively studied. The aim of our study was to evaluate the association between HUA and CI-CKD in patients with acute ST-Elevation Myocardial Infarction (STEMI) undergoing Percutanious Coronary Intervention (PCI). Methods:We prospectively studied 146 patients with acute STEMI undergoing PCI. According to serum uric acid (SUA), patients were divided into 2 groups, normouricemic group (Group 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…19 Likewise, a study by Abdollah et al conducted on 146 patients with acute STEMI underwent primary PCI concluded that 8.8% of the patients experienced developed CIN, 14.1% hyperuricemia and 2.94% with normal uric acid had a significant difference and concluded that elevated uric acid was associated with higher risk of CIN in the STEMI patients with normal serum creatinine after PCI. 25 This conflict can be explained so that that the patients in the present study had generally lower risk. Most of the patients in the present study had good kidney function as 73.5% had GFR>60 mL/min.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…19 Likewise, a study by Abdollah et al conducted on 146 patients with acute STEMI underwent primary PCI concluded that 8.8% of the patients experienced developed CIN, 14.1% hyperuricemia and 2.94% with normal uric acid had a significant difference and concluded that elevated uric acid was associated with higher risk of CIN in the STEMI patients with normal serum creatinine after PCI. 25 This conflict can be explained so that that the patients in the present study had generally lower risk. Most of the patients in the present study had good kidney function as 73.5% had GFR>60 mL/min.…”
Section: Discussionmentioning
confidence: 64%
“…Most of the articles in this subject are about acute condition like ST elevation MI (STEMI) or acute coronary syndrome. 5,7,19,[25][26][27] The important point of this study compared to other studies was as which this study examined just elective procedures and excluded all the primary PCI and urgent angiography cases. Meanwhile, the present study had enough time to eliminate the nephrotoxic drugs and give enough prophylaxis hydration to all the patients.…”
Section: Introductionmentioning
confidence: 99%